Task-based material design for academic purposes: Learners' English writing skill improvement - Audi Yundayani; Lidwina Sri Ardiasih (Universitas Syiah Kuala, 2021)
English Writing for Academic Purposes (EWAP) seems daunting for higher education students in the Indonesian context. Genuinely, the ability of EWAP is one of the study skills required in the academic field. Preliminary research has shown that EWAP materials have not been identified based on students’ needs. This study focuses on the students’ need analysis of the EWAP materials, including confirming the quality of the task-based material design that enhances the students’ skills of the EWAP. The study used the educational research and development method, involving non-English learners from a private college in Indonesia. Researchers used the test, the semi-structured interview, and the questionnaire as instruments. The observation was also carried out to describe implementing the task-based material design of the EWAP. The results indicate that students need task-based material as an authentic EWAP material that focuses on learning to communicate through interaction. It also gives them the ability to focus not just on the use of languages but also on the learning process itself. The task-based EWAP materials have a significant influence on the development of students’ writing skills. As a result, this approach is well suited to foster a learning desire to write in a context-approximately as a means of expressing their intentions. Besides, the study’s findings show that students were very enthusiastic about engaging in the learning process.